Height Reliability-Based Analysis of Woven Bamboo Mat Reinforced Mechanically Stabilized Earth Wall in Temporary Railway Embankment - Faris, Fikri; Adi, Agus Darmawan (Penerbit UTM Press, 2022)
Railway is a main transportation to sustain the fast-growing population and economy in many countries. Developing railway infrastructures, such as additional tracks, without disturbing daily operations often requires temporary mechanically stabilized earth as embankment construction. This paper discussed woven bamboo mat (WBM) as a highly potential local material that can be used in mechanically stabilized earth construction in such condition. Considering that WBM has a wide variation in tensile strength, this study determined the reliable railway embankment height through reliability-based analysis. First-order reliability method (FORM) was adopted to estimate the probability of failure (pF). The results of FORM were compared with the results of Monte Carlo simulation (MCS). The results showed positive trends in pF against increasing height, and the effective tensile capacity factor R negatively affected pF. The theoretically undegradable tensile strength in the design (R = 1.00) could increase the reliable height up to 12 m when sv = 0.2 m. Comparison between the FORM and MCS results showed that the pF calculated by FORM conformed with those computed by MCS. This study provided some insights and opened the opportunity for further research on other potential local materials as geomechanics reinforcement.